Citizen science in maritime archaeology : the power of public engagement - Scott-Ireton, Della A.; Jones, Jennifer E. (Archaeologist); Raupp, Jason T. (Jason Thomas); McKinnon, Jennifer F. (Jennifer Faith), 1974- (University Press of Florida, 2023)
"This volume addresses the ways maritime archaeologists have engaged citizen scientists, presenting examples of projects and organizations that have involved volunteers in the important work of gathering and processing data"--